Fisiologia, qualidade e produtividade da videira cv Syrah em diferentes estratégias de irrigação no semiárido - Teixeira, Rafael Pombo [UNESP] (2015)
The production of fine quality wines requires detailed studies of various agronomic practices. One is the irrigation management, especially when the vine is grown in areas with low rainfall as the Brazilian semiarid. Hypothetically, the water deficit from the phenological stage of closed cluster improves grape quality for wine. Thus, the objective was to evaluate the effect of irrigation strategies with water deficit on plant physiology and yield, and berry quality of wine vine cv. Syrah in the Lower Middle São Francisco Valley. The experiment was carried out at Embrapa Tropical Semi-Arid, in Petrolina, State of Pernambuco, Brazil, for three growing seasons (April 10 to August 9, 2013 - seson 5, October 8, 2013 to January 28, 2014 - season 6, and 7 May to September 3, 2014 - season 7), with 3 treatments and 4 repetitions. The treatments were: full irrigation (FI), where the application of water by drippers was based on the replacement of the crop evapotranspiration throughout the whole season; regulated deficit irrigation (RDI), where irrigation was interrupted in the closed cluster phenological phase, but eventually performed as the soil moisture monitoring in the effective rooting depth of vine, and deficit irrigation (DI), where irrigation was interrupted in closed cluster phase, continuing without water application to harvesting. Measurements of leaf water potential, gas exchange, and carbon isotopic composition in the vine, total soluble solids, pH, titratable acidity, anthocyanins, flavonoids, total polyphenols, tannins, and antioxidants activity in the berries, and number of cluster per plant, cluster mass per plant, average cluster mass, and vine yield were performed. The irrigation strategies RDI e DI promoted moderate water stress in plants, reducing water consumption and weight of 100 berries for the three seasons, reducing the titratable acidity in seasons 5 and 6, and increasing ...